Communicating change: the five sentiments of change perpective - Norhafezah Yusof,; Rosna Awang Hashim,; Jamaludin Badusah,; Mohd Majid Konting,; Chan, Kok Kian (Penerbit Universiti Kebangsaan Malaysia, 2012)
This research investigated the reactions of agents and recipients of change toward the introduction of a new co-curriculum model in Higher Learning Institutions (HLI)in Malaysia. The five sentiments of change framework was used to interpret this introduction of change in the HLI. Face-to-face interviewa were conducted with two groups of participants.The first group consisted of eight experts playing the role of change agents, and the second group was comprised of 13 directors of co-curriculum centers. The letter were the target recipients of the change process. Data colleted was categorized into themes, and the findings revealed significant contrasting reactions toward change between newly established and older universities. The present study is one of the few attempts to explain the impact of change on recipients in local HLI.